Need for prospective collection of experience and repeated samples in esophageal squamous cell carcinoma - Hamamoto, Yasuo (Journal of Thoracic Disease, 2018)
I appreciate the comments by Ajani, Pectasides, and RJ Kelly on our recent report (1). To my knowledge, two studies have evaluated checkpoint inhibitors related to esophageal squamous cell carcinoma (ESCC) (1,2). These two studies reported similar results with an objective response rate of approximately 20%, although selection bias should be considered. Several factors are thought to have influenced these results.